1999
DOI: 10.1021/ja982751v
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization Phenomena in the Sol−Gel Polymerization of α,ω-Bis(triethoxysilyl)alkanes and Incorporation of the Cyclic Structures into Network Silsesquioxane Polymers

Abstract: Intramolecular cyclizations during acid-catalyzed sol−gel polymerizations of α,ω-bis(triethoxysilyl)alkanes substantially lengthen gel times for monomers with ethylene (1), propylene (2), and butylene (3) bridging groups. These cyclization reactions were found, using mass spectrometry and 29Si NMR spectroscopy, to lead preferentially to monomeric and dimeric products based on six- and seven-membered disilsesquioxane rings. 1,2-Bis(triethoxysilyl)ethane (1) reacts under acidic conditions to give a bicyclic dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…This is in line with a study by Loy et al, who showed that propane-bridged ethoxysilanes react to a six-membered intramolecular condensation product which further dimerizes to a bicyclic product [23]. Because of the much lower network forming ability of this product, the growth rate of the hybrid silica particles is slowed down.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with a study by Loy et al, who showed that propane-bridged ethoxysilanes react to a six-membered intramolecular condensation product which further dimerizes to a bicyclic product [23]. Because of the much lower network forming ability of this product, the growth rate of the hybrid silica particles is slowed down.…”
Section: Discussionsupporting
confidence: 90%
“…In early studies on hybrid organosilica membranes based on BTESE, it was attempted to avoid the formation of condensed bicyclic carbosiloxanes [7,19]. Such oligomers have been reported to slow down or even inhibit gelation and may not become incorporated in a continuous network structure [22,23]. To lower the statistical chance of forming inert cyclic oligomers, BTESE was mixed with MTES in a 1:1 molar ratio.…”
Section: Sol-gel Synthesismentioning
confidence: 99%
“…To avoid a wide distribution of sizes in the sol, the hydrolysis is often carried out in two steps so that water-lean conditions are maintained throughout the process [24]. It is noted that in later studies hybrid organosilica membranes were mostly prepared from a single type of alkoxide precursor such as BTESE or bis(triethoxysilyl)methane (BTESM) [12,25,26], although condensation of monomers into relatively inert cyclic dimers that do not contribute to gel formation may have led to a decreased yield in these cases [22,27].…”
Section: Sol-gel Synthesismentioning
confidence: 99%
“…1000-1030 cm -1 upon cyclization). 34 As siloxane network formation proceeds, requiring the opening of the cyclic species, the energy of the v(Si-O) band again increases 34 to ca. 1040-1080 cm , within the region in which cyclized species are expected to occur.…”
Section: Resultsmentioning
confidence: 99%
“…A degree of condensation figure is difficult to calculate for BTESE materials, as cyclic T 2 and acyclic T 1 signals overlap 34 (analogous to the nomenclature for TEOSbased materials, T n is the fraction of the different T species with connectivity n; the subscript c indicates the signal from a cyclized product). Examination of the NMR data, however, clearly shows that CTAB-templated BTESE contains a higher relative contribution from T 0 and T 1 (cyclized) species than lipid-templated BTESE, consistent with an increase in condensation reactivity when lipid is present.…”
Section: Resultsmentioning
confidence: 99%